Diagnostic Accuracy of Endoscopic Trimodal Imaging and Chromoendoscopy for Lesion Characterization in Ulcerative Colitis. (8th September 2018) - Vleugels, Jasper L A; Rutter, Mathew D; Ragunath, Krish; Rees, Colin J; Ponsioen, Cyriel Y; Lahiff, Conor; Ket, Shara N; Wanders, Linda K; Samuel, Sunil; Butt, Faheem; Kuiper, Taeco; Travis, Simon P L; et al.
Abstract: Background: During surveillance colonoscopy of patients with long-standing ulcerative colitis [UC], a variety of dysplastic and non-dysplastic lesions are detected. The aim of this study was to address the diagnostic accuracy of endoscopic characterization of endoscopic trimodal imaging [ETMI] and chromoendoscopy [CE]. ETMI includes the combination of autofluorescence imaging [AFI], narrow band imaging [NBI] and white light endoscopy [WLE]. Methods: This is a pre-specified additional analysis of a multi-centre, randomized controlled trial that compared AFI with CE for dysplasia detection in 210 patients with long-standing UC [FIND-UC trial]. In the AFI arm, endoscopists used the ETMI system to record AFI colour, Kudo pit pattern using NBI and WLE for lesion characterization. For AFI, purple colour and ambiguous colour combined with pit pattern type III–V on NBI was considered dysplastic. Kudo pit pattern was described in the CE arm. For pit pattern description using NBI and CE, type III–V was considered dysplastic. Histology was the reference standard. Results: In total, 52 dysplastic and 255 non-dysplastic lesions were detected. Overall sensitivity for real-time prediction of dysplasia was 76.9% (95% confidence interval [CI] 46.2–95.0) for ETMI, and 81.6% [95% CI 65.7–92.3] for CE. Overall negative predictive value [NPV] for ETMI was 96.9% [95% CI 92.0–98.8] and 94.7% [90.2–97.2] for CE. Conclusions: Sensitivity for endoscopic differentiation of dysplastic lesions detected during surveillance of patients with long-standing UC seems limited using ETMI and CE. Future research is warranted as the high NPV indicates that these techniques are valuable for the exclusion of dysplastic lesions [NTR4062].